The implementation of guidelines in palliative care – a scoping review - Alexandra Ernst; Franziska Schade; Stephanie Stiel; Katharina van Baal; Franziska A. Herbst (BMC Palliative Care)
Abstract Background Guidelines are essential tools for ensuring high-quality healthcare. However, discrepancies exist between their availability and practical implementation. In the context of palliative care, the extent to which guidelines are implemented and the barriers and facilitators that influence this process remain unknown. Aim The present study aimed at systematically reviewing the international literature on the implementation of palliative care guidelines to evaluate factors that support or hinder implementation of palliative care guidelines globally. Method A scoping review was conducted following the methodological approach of Arksey and O’Malley (2005). After the formulation of research questions and development of a search string, relevant studies investigating the implementation of guidelines were identified and retrieved from the databases CINAHL, LIVIO, PubMed and Web of Science Core Collection on 4 January 2024. Two researchers independently selected articles for inclusion, employing a blinded process with predefined inclusion and exclusion criteria. The results were subsequently categorised deductively by the same researchers using Petermann’s (2014) taxonomy of implementation outcomes. The results were summarised and presented in tabular form. Results The search yielded 2,086 records, of which 1,252 were included in the title and abstract screening. Subsequently, 113 full-text articles were reviewed for eligibility, resulting in 29 articles deemed suitable for the final analysis. Six implementation outcomes were identified in the included literature: (1) acceptability (n = 15 articles), (2) adoption (n = 6 articles), (3) appropriateness (n = 9 articles), (4) feasibility (n = 9 articles), (5) fidelity/adherence (n = 14 articles) and (6) penetration (n = 14 articles). The majority of studies employed quantitative approaches (n = 22) and considered the perspective of healthcare professionals and their opinions regarding guideline implementation in palliative care. Only 4 articles considered patient related outcomes or the perspectives of the family caregivers. Ten articles reported on facilitators and barriers. Facilitators included healthcare professionals’ motivation and managerial support, while barriers primarily referred to time constraints and limited knowledge. Conclusions Guideline implementation in palliative care is highly variable. Future research should aim at comprehensively analysing facilitators of and barriers to this process, considering diverse implementation outcomes. For these evaluations, mixed-method approaches are recommended.